2018
DOI: 10.1051/bmdcn/2018080209
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of kidney cancer in Iran: a systematic review and meta-analysis

Abstract: Background: The incidence of kidney cancer from different areas of Iran was reported. Nevertheless, there is no available systematic reviews in this regard. Therefore, the present systematic review carried out to estimate the incidence rate of kidney cancer among Iranian people.Method: This systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) in September 2017. A search was concluded using Medline/ PubMed, Scopus, ScienceDirect, and Google… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Around 2% of adulthood and 2% -6% of childhood renal malignancies are RCC. In agreement with a previous study (22), the male PP (= 11.3) was 80.9% higher than the female PP (= 6.4) in the current study.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…Around 2% of adulthood and 2% -6% of childhood renal malignancies are RCC. In agreement with a previous study (22), the male PP (= 11.3) was 80.9% higher than the female PP (= 6.4) in the current study.…”
supporting
confidence: 94%
“…In the current study, there was a 20% increase in incidence from 2011 to 2015. The prevalence rates of renal pelvis and ureter cancers were 0.42 and 0.4, respectively, confirming that transitional cell carcinomas of the ureter and renal pelvis are relatively uncommon (3,(21)(22)(23)(24).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Cancer is the third most common cause of death in Iran [46]. So far, few studies have been conducted on the epidemiology of cancer in developing countries such as Iran [47][48][49][50]. The first study on cancer incidence in Iran dates back to the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the third leading cause of mortality in Iran (37)(38)(39)(40)(41)(42). GLOBOCAN 2012 reported that BC was the most common type of cancer among Iranian women (43).…”
Section: Discussionmentioning
confidence: 99%